Penerapan Model Pembelajaran Kooperatif tipe NHT (Number Head Together) untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Kelas X6 MAN 1 Makassar pada Materi Pokok Reaksi Reduksi- Oksidasi - Haedar Al-hapsi; Maryono Maryono; Alimin Alimin (ChemEdu, 2021)
The aim of this Classroom Action Research (CAR) is to recognize the systematically applied of the Cooperative Learning Model based NHT (Number Head Together) to increase the activities and the learning result of students in class X6 MAN 1 Makassar. There are four steps of CAR model such as (1) action planning, (2) implementation (3) observation, and (4) reflection. This research was held as many as two cycles. The data of this research result showed that, the learning with NHT model is able to increase the activities and the learning result of students in class X6 MAN 1 Makassar which is consist of 5 phase such as (1) Numbering phase, informing the aim, giving the perception, and motivating the students request. (2) Questioning phase and showing the information by explaining the available subject matter which is suitable with the learning indicators, (3) Head together phase was performed by providing the LKS and asking the students to answer the question together, (4) Answering phase was held by revealing the head number and asking the students to answer the question in the LKS which is suitable with group discussion result, (5) evaluation phase was held by proposing to the students to conclude the subject matter which was learned.